2D Seismic Reflection Study of Mishrif and Yamama Formations in East Nasiriya Area, Southern Iraq - Faisal, Mohammed S.; Ali, Kamal K. (Iraqi Journal of Science, 2021)
The structural division and stratigraphic estimation of the perceptible geological basin are the most important for oil and gas exploration. This study attempts to obtain subsurface geology in parts of east Nasiriya, southern Iraq using of seismic data and some adjacent well information for structural and stratigraphic interpretation. To achieve this goal, 2D seismic data in SEG-Y format were used with velocity and logging data. The seismic profile is then interpreted as a two-dimensional (time domain and depth domain) contour map, which is represented as a real subsurface geology.Reflectors from the Mishrif and Yamama Formations (Cretaceous period) were detected. According to the structural interpretation of the selected reflectors, TWT maps of the horizon were prepared, and depth maps were drawn, which show some noses structures in the study area. The seismic interpretation in this area confirmed the existence of certain stratigraphic features in the studied strata. Some distribution mounds and flat spots were also observed which similar to the characteristics of the Nasiriya oil field stratigraphic features that are the considered as hydrocarbon indicators.